Pengembangan Perangkat Pembelajaran Kooperatif Berbasis Teori Dienes Pada Materi Operasi Penjumlahan Dan Pengurangan Bilangan Bulat - Suryadi Ishak (Fakultas Keguruan dan Ilmu Pendidikan Univ. Al Asyariah Mandar Sulbar, 2013)
The Study aimed at developing learning package on the operation of addition and subtraction of integers subject material using cooperative learning based on Dienes theory. The learning package developed consisted of student’s book, student’s workbook, and the lesson plan. This study was a developmental research. The intended product of the study was cooperative learning package based on Dienes theory which fulfilled the criteria of valid, practical, and effective. The product consisted of four components, namely student’s book, student’s workbook, and lesson plan. Considering the time efficiency, the product was conducted in limited test and simulation; in other words, when developing the learning package, the instument related to the product was developed as well. The process of development of the learning package used 4-D which consisted of four phases (1) the defining, phase, which conducted a) pre-post analysis, b) student analysis, c) concept analysis, d) task analysis, e) specification of learning objective; (2) design phase, which conducted a) test arrangement, b) foemat selection, c) pre-desing of learning package (prototype), d) media selection; (3) development phase, which conducted a) experts interpretation, b) prototype tryout; (4) dissemination phase, which conducted limited socialization and dissemination of the learning package to obtain suggestion from teachers at Mathematics MGMP. The tryout was conducted once in grade IV SDN 066 Pekkabata. The result of the learning package obtained (1) the lesson plan and student’s workbook were in the category of extremely valid based on the evaluation of the experts, except the student’s book was in valid category, (2) practical because the result of learning management observation dane by the observer confirmed that the learning package was conducted well at the tryout, and (3) effective because it has fulfilled three criteria of effectiveness, which consisted of the classical mastery was achieved, students’ activeties have met the expectation, ind students dave positive response on the learning package and the implementation of learning activities